School-Based Diversity Education Activities and Bias-Based Bullying Among Secondary School Students. Issue 17 (September 2022) - Eisenberg, Marla E.; Gower, Amy L.; Brown, Camille; Nam, Yoon-Sung; Ramirez, Marizen R.
Bias-based bullying (e.g., bullying related to race, weight, sexual orientation) is a common experience among youth, yet few school-based prevention programs explicitly address this type of bullying. This study explores whether schools that offer diversity education activities have lower rates of bias-based bullying among students compared to schools that do not offer these activities. Data came from two sources: the 2018 CDC School Profiles Survey ( N = 216 schools) and the 2019 Minnesota Student Survey ( N = 64, 510 students). Multilevel logistic regression tested associations between diversity education activities (diversity clubs, lessons, or special events) and eight types of bias-based bullying among students, with attention to effect modification by relevant demographic characteristics. Students attending schools that offer a wider variety of diversity education opportunities had significantly lower odds of bullying about race, ethnicity, or national origin among boys of color ( OR = 0.89, CI: 0.80, 1.00), about sexual orientation for gay, bisexual, and questioning boys ( OR = 0.81, CI: 0.67, 0.97), and about disability for boys with a physical health problem ( OR = 0.86, CI: 0.76, 0.99). Attending a school with more types of diversity education activities may protect vulnerable students against specific types of bias-based bullying and advance health equity. A diversity education is recommended as a key component of antibullying efforts and policy.